The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/olq.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Sexually Transmitted Disease Screening Outside the Clinic—Implications for the Modern Sexually Transmitted Disease Program

Abstract: Background The development of noninvasive nucleic acid amplification tests for chlamydia and gonorrhea has facilitated innovation in moving sexually transmitted disease (STD) screening to nonclinical settings. However, limited data are available to inform local STD programs on evidence-based approaches to STD screening in nonclinical settings in the United States. Methods We conducted a systematic review of the literature published since 2000 related to chlamydia, gonorrhea, and syphilis screening in US corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
(51 reference statements)
2
27
0
1
Order By: Relevance
“…STD screening in correctional settings, for example, has been shown to be effective in identifying persons with undiagnosed bacterial STDs. 29 …”
Section: Discussionmentioning
confidence: 99%
“…STD screening in correctional settings, for example, has been shown to be effective in identifying persons with undiagnosed bacterial STDs. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Because this study was designed to inform WHO guidelines on the viability of self-sampling as an additional means to increase testing, articles that compared self-collection of samples by the location of intervention delivery (ie, self-collection at home vs self-collection at the clinic) were not included. These articles have been reviewed elsewhere 19 26–31…”
Section: Methodsmentioning
confidence: 99%
“…Self-collection approaches also have the potential to address some common barriers to clinician-dependent and/or clinic-based diagnosis, such as concerns around autonomy, inconvenience, stigma and lack of privacy 5 24 25. Systematic reviews have been conducted to compare STI testing programmes (some including self-collection methods) in home or non-clinic settings to those in clinic settings 19 26–31. However, no review to date has systematically compared self-collection of samples to clinician-collected methods for STI testing on programmatic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Major barriers of pharmacy-based screening included having to return the specimen to designated sites and lack of privacy 37,41 for patients and increased workload or feeling uncomfortable when offering the test, and lack of in store advertising for pharmacists 42 . The major benefits for patients included convenience, anonymity and no need for appointment, affordability 36 , shorter waiting times, and friendly non-judgmental attitude of pharmacists 43 . It was concluded that chlamydia screening in community pharmacies were feasible and could be a convenient option 43 .…”
Section: Individual and Interpersonal Levelsmentioning
confidence: 99%
“…The major benefits for patients included convenience, anonymity and no need for appointment, affordability 36 , shorter waiting times, and friendly non-judgmental attitude of pharmacists 43 . It was concluded that chlamydia screening in community pharmacies were feasible and could be a convenient option 43 .…”
Section: Individual and Interpersonal Levelsmentioning
confidence: 99%